IMPROVING MECHANISMS OF SPIRITUAL AND ETHICAL EDUCATION OF GENERAL SECONDARY SCHOOL STUDENTS - Gozal Eraliqizi Abdikhodirova (Web of Journals Publishing, 2023)
In this article, the scientific views on the improvement of the mechanisms of spiritual and moral education of general secondary school students are described. Scientific opinions are based on facts.
Keywords: value, culture, family, education, happiness, behavior, virtue, thinking, morality.